Tongkat ali root extract helps promote good oral health - Ramzi, Muhamad Iyad; Kosnin, Muhammad Hazzim; Faisal, Ghasak Ghazi; Arzmi, Mohd Hafiz; Kusumawardani, Anisa (2023)
Introduction: One of the important issues in oral healthcare is prevention of dental caries through maintenance of good oral hygiene. Despite the availability of many products in the market, dental caries and oral health problems still occur at high prevalence. Thus the introduction of natural remedies that can help promote oral health is of great importance. Eurycoma Longifolia Jack or Tongkat Ali roots have been known for a diverse spectrum of medicinal properties, one of which is antimicrobial activity. Thus our objectives were to test the activity of the root extract against important oral bacteria and fungi that are responsible for causing dental caries and other oral conditions. The roots of E. longifolia or Tongkat Ali have been used to in traditional medicine as well as supplements and food additives. Many chemical compounds have been detected in extracts of its roots which is believed to be responsible for its medicinal properties. In this study, our objectives were to study the effect of the E. Longifolia root extracts on the growth of Streptococcus Mutans, Lactobacillus and Candida Albicans isolated from saliva of adult patients with high caries risk.